2019
DOI: 10.3389/fmicb.2019.01381
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Analysis for the Optimization of Campylobacter Isolation From Chicken Carcasses Using Selective Media

Abstract: Since contaminated poultry meat is the major source of transmitting Campylobacter jejuni to humans, the isolation of Campylobacter from poultry carcasses is frequently performed in many countries as a baseline survey to ensure food safety. However, existing isolation methods have technical limitations in isolating this fastidious bacterium, such as a growth competition with indigenous bacteria in food samples. In this study, we compared the differences in microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Successful bacterial isolation relies on how effectively selective culture media can eliminate bacterial competitors while facilitating the growth of the target bacteria. Our previous studies demonstrated that each Campylobacter -selective medium makes substantial changes in the microbiome of enrichment cultures because of the selective pressure generated by antimicrobial supplements ( 11 , 12 ). Proteobacteria and Firmicutes are the major phyla after the enrichment of chicken carcasses with BB, whereas Proteobacteria and Fusobacteria were dominant after the enrichment with PB ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Successful bacterial isolation relies on how effectively selective culture media can eliminate bacterial competitors while facilitating the growth of the target bacteria. Our previous studies demonstrated that each Campylobacter -selective medium makes substantial changes in the microbiome of enrichment cultures because of the selective pressure generated by antimicrobial supplements ( 11 , 12 ). Proteobacteria and Firmicutes are the major phyla after the enrichment of chicken carcasses with BB, whereas Proteobacteria and Fusobacteria were dominant after the enrichment with PB ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that each Campylobacter -selective medium makes substantial changes in the microbiome of enrichment cultures because of the selective pressure generated by antimicrobial supplements ( 11 , 12 ). Proteobacteria and Firmicutes are the major phyla after the enrichment of chicken carcasses with BB, whereas Proteobacteria and Fusobacteria were dominant after the enrichment with PB ( 11 ). Commonly, antibiotic-resistant E. coli , such as ESBL-producing E. coli , is predominantly enriched in both BB and PB ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations